Elastomeric conductive hybrid hydrogels with continuous conductive networks. Issue 15 (8th March 2019) - Hu, Shiqian; Zhou, Lei; Tu, Lingjie; Dai, Cong; Fan, Lei; Zhang, Kejia; Yao, Tiantian; Chen, Junqi; Wang, Zhengao; Xing, Jun; Fu, Ruming; Yu, Peng; et al.
Abstract : The DA–PPy–GP ECHs with continuous conductive networks show high force and strain sensitivity. Abstract : Elastomeric conductive hybrid hydrogels (ECHs) combining conducting polymers with elastomeric hydrogels have recently attracted interest due to their wide range of applications in bioelectronics such as wearable or implantable sensing devices. However, the conductivity of ECHs is typically compromised when conductive polymers are used as fillers in hydrogel networks because the inherent limitations of ECHs severely restrict their applicability. Here, we significantly improved the electrical conductivity of ECHs by using a bioinspired catechol derivative, dopamine (DA), as the dopant and mediator for the in situ polymerization of conducting polypyrrole (PPy) within the elastomeric hydrogel dual-networks. In general, ECHs prepared by conventional methods tend to form separate island structures of conductive polymers dispersed within porous hydrogel matrices. We found that a continuous conductive PPy network prepared using the DA mediator facilitated fast electron transfer within the ECHs, which showed good elastomeric mechanical properties, excellent biocompatibility and high force- or strain-responsiveness suitable for implantable strain-sensing applications.